Evaluating staging habitat quality to advance the conservation of a declining migratory shorebird, Red Knot Calidris canutus. Issue 8 (27th May 2022) - Mu, Tong; Cai, Shangxiao; Peng, He‐Bo; Hassell, Chris J.; Boyle, Adrian; Zhang, Zhengwang; Piersma, Theunis; Wilcove, David S.
Abstract: Identifying where and when population 'bottlenecks' occur is critical to the conservation of migratory species, many of which are declining precipitously worldwide. Especially challenging is the evaluation of changes to staging sites. These sites are indispensable links in the migratory cycle but are typically used only briefly. We devised a field‐based approach to assess the quality and carrying capacity of a critical staging site in Nanpu, China, for the declining, migratory Red Knot ( Calidris canutus rogersi & C. c. piersmai ) during northward migration. The Nanpu tidal flat supports 50, 000–100, 000 Red Knots annually, and while there, the knots feed almost exclusively on the bivalve Potamocorbula laevis . We simultaneously monitored changes in the abundance of Red Knots and bivalves across this entire staging site in spring 2018. After taking into account potential competition with other shorebird species, we estimated that the Nanpu tidal flat was capable of supporting approximately 1.46–1.70 times the observed level of Red Knot usage of this site, and therefore is operating below, but close to, carrying capacity with respect to food resources for Red Knots. This result suggests that any further habitat loss or degradation at this site could harm the Red Knot population along the entire East Asian‐Australasian Flyway. Synthesis and applications . Quantitative monitoring and evaluation of habitat quality of staging sites are essential to successfully conserve declining migratory species. In particular, researchers and conservation practitioners should incorporate both population size and staging duration to more accurately assess the importance of different sites and to quantify how changes in staging habitat quality may translate into changes in the population sizes of migratory species at both local and global scales. Abstract : Quantitative monitoring and evaluation of habitat quality of staging sites are essential to successfully conserve declining migratory species. In particular, researchers and conservation practitioners should incorporate both population size and staging duration to more accurately assess the importance of different sites and to quantify how changes in staging habitat quality may translate into changes in the population sizes of migratory species at both local and global scales. 摘要: 全球的迁徙候鸟数量都在急剧下降。识别出影响它们种群数量变化的关键栖息地和生活史阶段，对于 保护这些快速减少的迁徙物种而言至关重要。尽管候鸟每年利用中停地的时间较为短暂，中停地在候鸟的迁徙和生存过程中却起着举足轻重的作用。然而，如何量化和评估中停地的栖息地质量及其对于候鸟 种群的影响却颇具挑战。 本研究设计了㇐套基于野外调查的中停地栖息地质量及环境承载力评估方案，并以每年春季北迁期间 在河北南堡滩涂停歇的红腹滨鹬 ( Calidris canutus rogersi & C. c. piersmai ) 作为研究对象，测试了该方案 的可行性。每年春天约有5‐10万只红腹滨鹬到访南堡，它们主要取食滩涂中的光滑河篮蛤 ( Potamocorbula laevis ) 进行能量补给。2018年春季，我们对整个南堡滩涂的红腹滨鹬和光滑河篮蛤数量 变化进行了持续监测。 将其他鸻鹬类的种间竞争影响考虑在内，南堡滩涂的红腹滨鹬环境承载力约为当年实际种群利用强度 的1.46‐1.70倍。综合分析表明，南堡滩涂上红腹滨鹬的食物利用强度十分接近其环境承载力，因此，当 地栖息地质量的变化可能会极大地影响整个东亚‐澳大利西亚迁飞区的红腹滨鹬种群数量。 综述和应用 :针对重要中停地的栖息地质量监测和评估对于保护那些数量快速下降的候鸟种群具有十 分重要的意义。在科学研究和实际保护工作中，人们尤其需要同时考虑整个迁徙季节中的中停地候鸟数 量变化及其停留时长，从而更为准确地评估不同中停地对于候鸟的重要性，进而定量化地研究和预测栖 息地质量变化将如何影响候鸟的种群数量。